Dimensi Maqashid Al-‘Adl dalam Peraturan Pemerintah Nomor 35 Tahun 2024 tentang Waralaba - Fatkhurrohman, Safiq; Nursobah, Achmad; Muhaini, Akhmad (AL-SULTHANIYAH, 2025)
Government Regulation No. 35 of 2024 on Franchising aims to create a fair and transparent business relationship between franchisors and franchisees. This study examines the application of the maqashid al-adl principles, particularly the principles of i’ṭā’ al-ḥuqūq (giving rights to those entitled), man‘ az-zhulm (preventing injustice), al-musāwah (equality), al-wuḍūh (clarity), and at-takāful (solidarity), in the regulation to ensure the creation of a fair system that benefits both parties. Descriptive qualitative research methodology is employed, examining the text of the regulation and associated legal papers. It is anticipated that this research would aid in the creation of just and sustainable franchising regulations as well as Islamic economic law. The practical implications of this research include strengthening transparency and accountability in franchising relationships and providing protection for franchisees' rights.